Job quality, health and at-work productivity - Arends, Iris; Prinz, Christopher; Abma, Femke I. (Paris, 2017)
"Many countries invest considerable resources into promoting employment and the creation of jobs. At the same time, policies and institutions still pay relatively little attention to the quality of jobs although job quality has been found to be a major driver of employee wellbeing and may be an important factor for work productivity. Eventually, job quality might also influence labour supply choices and lead to higher employment. Providing robust evidence for the relationship between job quality and worker productivity could make a strong case for labour market policies directed at the improvement of job quality. This paper reviews existing evidence on the relationship between the quality of the work environment and individual at-work productivity, defined as reduced productivity while at work, and assesses the effect of health on this relationship.